Mortality rates and division of labour in the leaf-cutting ant, Atta colombica - BROWN, MARK (My University, 2006)
Division of labor in social groups is affected by the relative costs and benefits of conducting different tasks. However, most studies have examined the dynamics of division of labor, rather than the costs and benefits that presumably underlie the evolution of such systems. In social insects, division of labor may be simplistically described as a source-sink system, with external tasks, such as foraging, acting as sinks for the work force. The implications of two distinct sinks ? foraging and waste-heap working ? for division of labor were examined in the leaf-cutting ant Atta colombica. Intrinsic mortality rates were similar across external task groups. Exposure to waste (a task-related environment) led to a 60% increase in the mortality rate of waste-heap workers compared to workers not exposed to waste. Given the small number of workers present in the waste-heap task group, such increases in mortality are unlikely to affect division of labor and task allocation dramatically, except perhaps under conditions of stress.
PUBLISHED
Keywords: social insects; task allocation; waste management; hygiene